An authentic learner-centered planetary health assignment: A five-year evaluation of student choices to address Sustainable Development Goal 13 (Climate Action) - McLean, Michelle; Phelps, Charlotte; Smith, Jessica; Maheshwari, Neelam; Veer, Vineesha; Bushell, Dayna; Matthews, Richard; Craig, Belinda; Moro, Christian (Frontiers in Public Health, 2022)
A Code Red has been declared for the planet and human health. Climate change (e.g., increasing temperatures, adverse weather events, rising sea levels) threatens the planet's already declining ecosystems. Without urgent action, all of Earth's inhabitants face an existential threat. Health professions education should therefore prepare learners to not only practice in a changing world, but authentic educational activities should also develop competencies for global and planetary citizenship. Planetary health has been integrated across the five-year Bond University (Australia) medical curriculum. It begins in the second week of Year 1 and ends with a session on Environmentally Sustainable Healthcare in the General Practice rotation in the final year. The purpose of this article is to describe the outcomes of the first 5 years (2018–2022) of a learner-centered planetary health assignment, underpinned by the 2030 United Nations (UN) Sustainable Development Goals (SDGs), in the second year of a five-year medical program. Using systems and/or design thinking with a focus on SDG13 (Climate Action) plus a second SDG of choice, self-selected teams of 4–6 students submit a protocol (with feedback) to develop a deliverable “product” for an intended audience. Data analysis of the first 5 years of implementation found that the most frequently selected SDGs in addition to SDG13 were: SDG12 Sustainable Production and Consumption (41% of teams), mostly relating to healthcare emissions and waste; SDG3 Health and Well-being (22%), generally involving the impact of air pollution; and SDG6 Clean Water and Sanitation (15%). A survey at the concluding conference garnered student feedback across various criteria. The planetary health assignment is authentic in that teams provide solutions to address climate change. Where appropriate, final “products” are sent to local or federal ministers for consideration (e.g., policy proposals) or integrated into the curriculum (e.g., learning modules). We believe that the competencies, attitudes, and values fostered through engagement with planetary health. Throughout the medical program, as evidenced by their evaluations, stands students in good stead to be change agents, not only in clinical practice but in society. An awareness has been created about the need for planetary citizenship in addition to global citizenship.